PRELIMINARY CHECKLIST OF BEETLES ASSEMBLAGES (ORDER: COLEOPTERA) FROM LIMESTONE FORESTS IN SOUTHERN SARAWAK, MALAYSIA - Tan, Wei Lim; Nurfarida Anum, Zainaddin; Siti Nurlydia, Sazali; Annette Aurelia, Molujin; Zulrafie, Hambri; Ratnawati, Hazali (Faculty of Science and Technology (FST) , Unversiti Kebangsaan Malaysia (UKM), 2023)
Beetles are becoming important subjects of ecological interest for conservation studies due to their high biodiversity and distribution, despite rapid urbanisation and deforestation activities. This study initiates to present a preliminary checklist of beetles from limestone forests in Southern Sarawak, Malaysia which included four selected localities within Bau and Padawan districts, namely, Mount Serumbu (Bau), Fairy Cave Nature Reserve (Bau), Raya Cave (Padawan) and Temurang Cave (Padawan). Each sampling trip was conducted for five consecutive days, using both active and passive methods. As a result, a total of 786 individuals representing 191 species (56 confirmed species and 135 morphospecies) from 81 genera under 57 subfamilies and 23 families were successfully recorded. Overall, the most speciose family was represented by Carabidae (39 species; 20.42%), followed by Scarabaeidae (32 species; 16.75%), Chrysomelidae (29 species; 15.18%), and Tenebrionidae (22 species; 11.52%), respectively. Meanwhile, Carabidae was the most abundant family (175 individuals; 22.26%), followed by Scarabaeidae (126 individuals; 16.03%), Chrysomelidae (124 individuals; 15.78%), and Tenebrionidae (116 individuals; 16.03%), respectively. In general, Triplatoma macleayi (Erotylidae) was the most abundant species with a total of 56 individuals (7.12%), followed by Amarygus sp. 1 (Tenebrionidae) with 39 individuals (4.96%). To conclude, this study is hopefully beneficial to document the diversity and abundance of beetles within limestone areas and useful to the local authority in identifying potential hotspot area(s) for biodiversity conservation and effective management practice. However, it is recommended that future studies should include other limestone forests, covering areas in the central and northern regions of Sarawak.